Restorative Justice dalam Sengketa Ketenagakerjaan: Alternatif Penyelesaian di Luar Litigasi - Atmari; Sudjai (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The settlement of labor disputes in Indonesia continues to be dominated by formal, procedural, and adversarial mechanisms. Although various dispute resolution avenues are available ranging from bipartite negotiations and mediation to litigation these mechanisms have not effectively produced substantively fair outcomes nor sustained industrial relations. This limitation reveals a structural weakness in the existing legal framework, which prioritizes procedural certainty over relational justice. This study aims to examine the normative construction of labor dispute resolution within the Indonesian legal system, assess the conceptual relevance of restorative justice in industrial relations, and formulate a reconstructed dispute resolution model grounded in restorative principles. The research employs a normative legal method using statute and conceptual approaches. The findings indicate a normative gap in accommodating restorative justice within the current legal framework, particularly under Law Number 2 of 2004 on Industrial Relations Dispute Settlement. Conceptually, restorative justice aligns with the continuous and interdependent nature of employment relations by emphasizing dialogue, participation, and relational recovery. This study concludes that the existing system fails to accommodate restorative values, thereby necessitating a reconstruction of legal norms. It recommends integrating restorative principles into dispute resolution mechanisms, strengthening mediator roles, and promoting a paradigm shift toward dialogical and participatory justice.